2015
DOI: 10.6061/clinics/2015(11)03
|View full text |Cite
|
Sign up to set email alerts
|

Can mastalgia be another somatic symptom in fibromyalgia syndrome?

Abstract: OBJECTIVE:The purposes of this study were to determine the coexistence of mastalgia and fibromyalgia, to investigate the effects of this combination on pain patterns, and to discuss the status of breast pain in the diagnostic algorithm of fibromyalgia syndrome.METHODS:Sixty-one female patients reporting breast pain during the last three months and 53 female patients diagnosed with fibromyalgia syndrome were enrolled in this study. The Breast Pain Questionnaire was administered to all participants in the mastal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The use of EMG to obtain information about muscle response or electrical activity to a nerve's stimulation of a muscle provides information to the clinician regarding many conditions such as muscle aches, muscle weakness, anomalies related to muscle movements, and muscle atrophy (24,29). Although many studies have evaluated the relationship between fibromyalgia and the nociceptive flexion reflex, we did not find any study evaluating the relationship of nociceptive flexion reflex with mastalgia (30,31). Furthermore, only a few studies have evaluated the relationship between fibromyalgia and CSP, and we found no study investigating the relationship between mastalgia and CSP (25)(26)(27).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The use of EMG to obtain information about muscle response or electrical activity to a nerve's stimulation of a muscle provides information to the clinician regarding many conditions such as muscle aches, muscle weakness, anomalies related to muscle movements, and muscle atrophy (24,29). Although many studies have evaluated the relationship between fibromyalgia and the nociceptive flexion reflex, we did not find any study evaluating the relationship of nociceptive flexion reflex with mastalgia (30,31). Furthermore, only a few studies have evaluated the relationship between fibromyalgia and CSP, and we found no study investigating the relationship between mastalgia and CSP (25)(26)(27).…”
Section: Discussionmentioning
confidence: 80%
“…In their study including 50 patients with mastalgia and 50 with fibromyalgia, Genc et al (31) reported that 36% of mastalgia patients met fibromyalgia criteria, and 42% of fibromyalgia patients had mastalgia complaints. In another study by Sen et al (30), 47.2% of 53 patients with fibromyalgia had mastalgia and 37.7% of 61 patients with mastalgia met the diagnostic criteria for fibromyalgia syndrome (30).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[ 6 , 7 ] Musculoskeletal components that are beneath the breast may have disorders mimicking and/or confused with mastalgia. [ 8 , 9 ] Myofascial pain syndrome (MPS) may be a possible reason of mastalgia for patients without primary breast disorder. To our knowledge, there is no study in the literature regarding the relationship between MPS and mastalgia.…”
Section: Introductionmentioning
confidence: 99%
“…This type of pain is not associated with malignancy [8]. Benign causes of breast pain are numerous and include hormonal variations, larger cup size, ill-fitting or unsupportive bra, lower levels of fitness or activity, fibromyalgia, cysts, periductal mastitis, stretching of Cooper ligaments, fat necrosis, surgery, Mondor disease, diabetic mastopathy, duct ectasia, musculoskeletal disease, referred nerve root pain from degenerative spinal changes, herpes zoster, heart disease, biliary pain, and peptic ulcer [3,5,[16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introduction/backgroundmentioning
confidence: 99%